Bilateral Complex Regional Pain Syndrome after Fracture of Bilateral Tibia and Fibula - Senem Şaş; Zeynep Karakuzu Güngör; Hatice Rana Erdem; Figen Tuncay (Türk Osteoporoz Dergisi)
Complex regional syndrome type 1 (CRPS-1) is a painful clinical condition. It occurs after a painful event and characterized by allodynia, hyperalgesia, edema, abnormalities in skin blood flow and abnormal sudomotor activity. When CRPS-1 is associated with nerve injury, it is defined as CRPS-2. Central and peripheral theory are responsible in etiopathogenesis of CRPS-1. Generally it occurs in the injured limb. But, it may ocur in the opposite extremities. In this article, we present a case developing bilateral CRPS-1 after bilateral tibia and fibula fracture by reviewing current literatüre.